2021
DOI: 10.38104/vadyba.2021.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitude Towards Volunteering in Sport

Abstract: This article deals with the issue of volunteering in sport. Participating in sport volunteering is beneficial because it increases social integration, social participation, and social awareness. With the growing importance of volunteering for both the volunteer and society, sport volunteering is becoming a phenomenon that fosters and encourages volunteer initiative. In Lithuania, volunteering in sport is still developing, so it is important to research the motivation of volunteers and direct their energy to vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In their responses, the employers stressed that specific soft skills, particularly teamwork and the ability to progress, were imperative due to the increased competitive pressure. Researchers also focused on examining the need for soft skills in specific areas of activity, such as engineering and information technology (Matturro, Raschetti, Fontán, 2019;Holtkamp, Jokinen, Pawlowski, 2015;Stewart, Yeom, Stewart, 2020), finance and bookkeeping (Rebele, Pierre, 2019;Dolce, Federica, Maurizio, Chiara, 2020), medicine (Sancho-Cantus, Cubero-Plazas, Botella Navas, Castellano-Rioja, Cañabate Ros, 2023;Goldman, Wong, 2020;Myren, van der Aa, Pula, Scheele, 2019), and sport management (Budreikaitė, Kontautienė, Tamoševičienė, Grigolienė, 2021). The research findings obtained demonstrated unequivocally that the soft skills acquired by employees set them apart from their peers, and were essential for excelling at performing direct duties in all areas of activity and at all levels.…”
Section: Introductionmentioning
confidence: 99%
“…In their responses, the employers stressed that specific soft skills, particularly teamwork and the ability to progress, were imperative due to the increased competitive pressure. Researchers also focused on examining the need for soft skills in specific areas of activity, such as engineering and information technology (Matturro, Raschetti, Fontán, 2019;Holtkamp, Jokinen, Pawlowski, 2015;Stewart, Yeom, Stewart, 2020), finance and bookkeeping (Rebele, Pierre, 2019;Dolce, Federica, Maurizio, Chiara, 2020), medicine (Sancho-Cantus, Cubero-Plazas, Botella Navas, Castellano-Rioja, Cañabate Ros, 2023;Goldman, Wong, 2020;Myren, van der Aa, Pula, Scheele, 2019), and sport management (Budreikaitė, Kontautienė, Tamoševičienė, Grigolienė, 2021). The research findings obtained demonstrated unequivocally that the soft skills acquired by employees set them apart from their peers, and were essential for excelling at performing direct duties in all areas of activity and at all levels.…”
Section: Introductionmentioning
confidence: 99%